الاضطرابات اللغويَّة لدى أطفال طيف التوحد وسبل تذليلها من خلال تصميم برنامج رسوم متحركة موجهة إليَّهم - هدى العيش (My University, 2025)
Abstract This research addresses a crucial topic—one of the most significant linguistic challenges faced by children with autism spectrum disorder—and explores ways to overcome it through animated programs specifically designed for them. The study is organized into two chapters. The first is a theoretical chapter entitled "Language Disorders in Children with Autism Spectrum Disorder and Ways to Overcome Them through Animation: Foundations and Concepts," comprising three sections. The first section discusses the concept of language disorders and the most prominent factors contributing to their development. The second section examines the key manifestations of language disorders in children with autism spectrum disorder. The third section explores the fundamental principles of animation. The second chapter is practical in nature. It seeks to reduce language disorders in children with autism spectrum disorder through simple and repetitive animated programs targeted at them. These programs aim to support the gradual improvement of the child’s language skills. The study concludes that language disorders in children on the autism spectrum are varied, encompassing both expressive and receptive impairments. These disorders can be alleviated through the use of diverse visual and auditory media --------------- تطرقت في هذا البحث إلى قضيَّة هامة من أهم القضايا اللغويَّة، والتي تتمثل في مظاهر الاضطرابات اللغوية لدى أطفال طيف التوحد و كيفية تذليلها من خلال برامج رسوم متحركة موجهة إليَّهم، تناولت في هذا الموضوع فصلين مهميَّن فصل نظري معنون ب "الاضطرابات اللغويَّة لدى أطفال طيف التوحد ودور الرسوم المتحركة في تذليلها الأسس والمفاهيم" يتضمن ثلاثة مباحث أساسيَّة المبحث الأول تطرقت فيه إلى مفهوم الاضطرابات اللغويَّة وأهم العوامل الناتجة عنها، المبحث الثاني تناولت في أهم مظاهر الاضطرابات اللغويَّة لدى أطفال طيف التوحد، المبحث الثالث تطرقت في إلى أهم الأساسيَّات في الرسوم المتحركة، أمَّا الفصل الثاني من الدراسة الفصل التطبيقي حاولت فيه تذليل الاضطرابات اللغويَّة لدى أطفال طيف التوحد بواسطة برامج رسوم متحركة موجهة إليَّهم، تتميز ببساطتها وتكرارها مما يساعد في تحسين مهارات اللغة لدى الطفل بشكل تدريجي. مما خلص إليه البحث أن مظاهر الاضطرابات اللغويَّة لدى أطفال طيف التوحد متعددة سواء أكانت اضطرابات لغة تعبيريَّة أو اضطرابات لغة استقباليَّة، يمكن تذليلها بواسطة الوسائط البصريّة والسمعيَّة المتعددة. ---------------- Cette recherche aborde une question importante dans le domaine des troubles du langage, qui se manifeste chez les enfants atteints de trouble du spectre autistique, et examine comment les traiter à travers des programmes animés dirigés. Le sujet est développé dans un chapitre théorique intitulé : « Les troubles du langage chez les enfants atteints de trouble du spectre autistique ». Le mémoire comprend trois chapitres principaux : Le premier chapitre aborde les concepts fondamentaux liés au thème et les facteurs contribuant à l’apparition des troubles du langage chez les enfants atteints de trouble du spectre autistique. Le deuxième chapitre traite des bases théoriques des programmes animés dirigés. Le troisième chapitre présente l’aspect pratique, dans lequel une tentative a ét faite d’aborder les troubles du langage chez les enfants atteints de trouble du spectre autistique à l’aide de programmes animés dirigés, répétés et variés, afin d'améliorer la communication de l’enfant de manière générale. Les résultats de cette recherche montrent que l’utilisation de programmes animés dirigés aide les enfants à surmonter leurs troubles du langage, et peuvent être utilisés comme stratégie éducative alternative à adopter dans les classes spécialisées.
Keywords: language disorders; autism spectrum disorder; animated programs; الاضطرابات اللغويَّة، اضطراب طيف التوحد، الرسوم المتحركة; Troubles du langage; trouble du spectre autistique; programmes animés dirigés.